Pengaruh Desain User Interface (UI) Terhadap User Experience (UX) Dalam Mendengarkan Musik Online - Cannavaro, Afiq Fadhil; Widyassari, Adhika Pramita (JIIFKOM (Jurnal Ilmiah Informatika dan Komputer), 2025)
Digital music streaming services are increasingly popular and have become part of the lifestyle of modern society. One of the important factors that influence user comfort and satisfaction in using digital music applications is the interface design (user interface). This study aims to determine the effect of interface design (UI) on the experience (UX) of listening to music online. The method used is a quantitative approach with a survey technique on 100 respondents who are active users of Spotify, JOOX, and YouTube Music. The independent variable studied is interface design, while the dependent variable is user experience. Data were collected through questionnaires and analyzed using simple linear regression. The results showed that the average overall score reached 4.26 which is included in the "very good" category, with scores such as: interactive feature aspects (score 4.45), visual appearance (score 4.35), ease of navigation (score 4.20), etc., This proves that interface design has a significant influence on the music listening experience and plays an important role in creating a positive user experience.